Multifunctional Magnetic Oxide Nanoparticle (MNP) Core-Shell: Review of Synthesis, Structural Studies and Application for Wastewater Treatment - Ebenezer C. Nnadozie; Peter A. Ajibade (Molecules, 2020)
The demand for water is predicted to increase significantly over the coming decades; thus, there is a need to develop an inclusive wastewater decontaminator for the effective management and conservation of water. Magnetic oxide nanocomposites have great potentials as global and novel remediators for wastewater treatment, with robust environmental and economic gains. Environment-responsive nanocomposites would offer wide flexibility to harvest and utilize massive untapped natural energy sources to drive a green economy in tandem with the United Nations Sustainable Development Goals. Recent attempts to engineer smart magnetic oxide nanocomposites for wastewater treatment has been reported by several researchers. However, the magnetic properties of superparamagnetic nanocomposite materials and their adsorption properties nexus as fundamental to the design of recyclable nanomaterials are desirable for industrial application. The potentials of facile magnetic recovery, ease of functionalization, reusability, solar responsiveness, biocompatibility and ergonomic design promote the application of magnetic oxide nanocomposites in wastewater treatment. The review makes a holistic attempt to explore magnetic oxide nanocomposites for wastewater treatment; futuristic smart magnetic oxides as an elixir to global water scarcity is expounded. Desirable adsorption parameters and properties of magnetic oxides nanocomposites are explored while considering their fate in biological and environmental media.